Social identity - Jenkins, Richard 1952- (Routledge, 1996)
Social Identity provides a clearly-written accessible introduction to sociological and social anthropological approaches to identity. Looking at the work of Mead, Goffman and Barth, this book makes clear their relevance to everyday life. Insisting that reflexive self identity is not a modern phenomenon, the core argument is that individual and collective identity can both be understood using the same model, as 'internal' and 'external' processes. Social Identity brings together sociological and social anthropological theories of identity, and makes an original contribution to social theory. Focusing on identity as individual and collective, this book brings us a fresh perspective on the relationship between the individual and society. This book provides an essential guide to the concept of social identity, offering students critical discussions of Schutz, Berger and Luckman, Becker, Anthony Cohen, Giddens, Bourdieu and many others.
Keywords: Mudanca social; Sistema social; Sociale identiteit; Sociologia (filosofia e teoria); Group identity; Soziale Identität